2017
DOI: 10.1007/s00467-017-3694-4
|View full text |Cite
|
Sign up to set email alerts
|

Citrate versus heparin anticoagulation in continuous renal replacement therapy in small children

Abstract: BackgroundCitrate is preferred over heparin as an anticoagulant in adult continuous renal replacement therapy (CRRT). However, its potential adverse effects and data on use in CRRT in infants and toddlers is limited. We conducted a prospective study on using citrate in CRRT in critically ill small children.MethodsChildren who underwent CRRT with the smallest filter in our PICU between November 2011 and November 2016 were included. Both heparin and citrate were applied according to a strict protocol. Our primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…Furthermore, citrate dosing is based on blood flow, which is disproportionately high (as per kg BW) in small children, due to technical limitations of adult CRRT devices. Thus frequent citrate accumulation (70% patients, 25% of circuits) in our population was to be expected and is also reported in some other studies (30% of the patients had t/iCa > 2.4 in Rico et al), especially in patients with liver failure (70% of patients had t/iCa > 2.5 for > 48 h in Rodriguez et al), but many other studies report no problems with citrate accumulation …”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, citrate dosing is based on blood flow, which is disproportionately high (as per kg BW) in small children, due to technical limitations of adult CRRT devices. Thus frequent citrate accumulation (70% patients, 25% of circuits) in our population was to be expected and is also reported in some other studies (30% of the patients had t/iCa > 2.4 in Rico et al), especially in patients with liver failure (70% of patients had t/iCa > 2.5 for > 48 h in Rodriguez et al), but many other studies report no problems with citrate accumulation …”
Section: Discussionsupporting
confidence: 88%
“…3,9 In contrast, effect of citrate is limited to the extracorporeal circuit and does not induce thrombocytopenia, which also reduces bleeding risk. 10 However, citrate carries the risk of metabolic disturbances (alkalosis or acidosis) and electrolyte imbalances (hypercalcemia, hypocalcemia, and hypernatremia). 4,11 Although there are many studies in adult patient groups, very few controlled trials and observational studies have been carried out in pediatric patients on CRRT with citrate.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the concentration of sodium citrate in vitro was higher (4 mmol/L) than that reported in other studies using calcium-free substitutes (2.5–3.5 mmol/L). [6,8,11] Additionally, there were only 2 sessions (1.9%) with T/iCa 2+ > 2.5, which usually indicated citrate accumulation. [1719] This suggested that most children could tolerate a sodium citrate concentration of 4 mmol/L in the extracorporeal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have shown that RCA in CRRT could be used safely and effectively to treat children. [211] However, this technique is complicated by the lack of commercially available physiological fluids, the various protocols that use different solutes and strategies, and the meticulous adjustment of citrate and calcium perfusions based on blood flow. [2] Because 4% citrate solution contains high levels of calcium and sodium ions, the substitute should contain less sodium and less or no bicarbonate to avoid acid–base imbalances and hypernatremia.…”
Section: Introductionmentioning
confidence: 99%